Linear algebra a modern introduction - Poole, David (Cengage Learning, 2015)
Emphasizes a vectors approach and prepares students to make the transition from computational to theoretical mathematics. This book includes applications drawn from a variety of disciplines, which reinforce the fact that linear algebra is a valuable tool for modeling real-life problems.